Determinantes del proceso de emprendimiento empresarial femenino en el Perú - León Mendoza, Juan (2010)
This article aims to identify the variables that determine the probability that the adult Peruvian woman head and householder decides to start any business or own enterprise. With information from the National Household Survey (ENAHO), using the econometric technique of logit model and odds ratios, we find that the probability that a woman start a business is determined, in a direct sense, by age, personal social capital, the family size; and, conversely, the level of education attained and household per capita income.